Pengaruh Kontribusi Pembiayaan Mikro Modal Kerja di dalam Lembaga Keuangan Perbankan Syariah terhadap Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) di Kota Palembang (Studi Kasus Bank Syariah Indonesia KC Demang) - Faadhilla Putri Aryanti; Fachradita Nurhalizah; Hayatull Jannah (Universitas Batanghari Jambi, 2022)
Islamic banking is a banking system whose implementation is based on Islamic law. Financial institutions whose operational activities and products adhere to Islamic principles based on Islamic principles Quran and Hadith. The characteristics of Islamic banking are actually based on the core product of profit-sharing financing developed in the product musyarakah and mudharabah financing. The presence of Islamic banking should have a major impact on real sector growth. One unit Businesses that need to be developed to encourage real sector growth are Micro, Small and Medium Enterprises (MSMEs) which in the current national economy has a very important position, because of its contribution to employment and Gross Domestic Product (GDP). As well as its flexibility and toughness in facing an economic crisis. The role of working capital microfinance plays an important role in providing guidance to (MSMEs) to develop businesses, provide consulting on business development and facilitating the existence of a place of business in the Palembang city.